Transcription factor paired related homeobox 1 (PRRX1) activates matrix metalloproteinases (MMP)13, which promotes the dextran sulfate sodium-induced inflammation and barrier dysfunction of NCM460 cells. Issue 1 (1st January 2022) - Zhang, Xiujing; Ma, Lizhuan; Shen, Ying; Zhang, Chao; Hou, Bingxu; Zhou, Yanli
ABSTRACT: Paired related homeobox 1 (PRRX1) is a newly identified transcription factor that regulates the expression of various genes. We aimed to investigate the roles of PRRX1 and Matrix metalloproteinases (MMP)13 in dextran sulfate sodium (DSS)-induced inflammation and barrier dysfunction of NCM460 cells. PRRX1 expression in the mucosal tissues of patients with ulcerative colitis was analyzed using the GSE87466 microarray. PRRX1 and MMP13 expression was examined using Western blotting and RT-qPCR following the exposure of the NCM460 cells to DSS. The JASPAR database was used to predict the binding sites of PRRX1 to the MMP13 promoter, which was verified by luciferase reporter and chromatin immunoprecipitation assays. MMP13 expression was then detected following PRRX1 silencing or overexpression. The levels of inflammatory factors were determined using ELISA. Finally, the expression of intestinal barrier function-related proteins was evaluated using Western blotting and cellular permeability was detected by Transepithelial electrical resistance. PRRX1 was upregulated in the mucosal tissue samples of patients with UC. DSS induction upregulated PRRX1 and MMP13 expression. PRRX1 bound to the promoter of MMP13, which was further supported by the decreased expression of MMP13 observed following PRRX1 knockdown and its increased expression following PRRX1 overexpression. Furthermore, PRRX1 deletion decreased TNF-α, IL-1β and IL-6 levels in the DSS-challenged NCM460 cells, which were subjected to MMP13 overexpression. Moreover, PRRX1 silencing upregulated ZO-1, occludin and claudin-1 expression and elevated the TEER value, whereas MMP13 overexpression attenuated these effects. Collectively, PRRX1 activates MMP13, which in turn promotes the DSS-induced inflammation and barrier dysfunction of NCM460 cells.